Globalization's limits to the environmental state? Integrating telecoupling into global environmental governance. Issue 1 (2nd January 2016) - Lenschow, Andrea; Newig, Jens; Challies, Edward
Abstract : Globalization entails increased interdependence and interconnectivities among distal regions and social-ecological systems. This global interregional connectedness – telecoupling – gives rise to specific sustainability challenges, which require new governance solutions. Moving beyond 'scaling-up' governance to address global environmental problems, and exploring the implications of telecoupling for state-led environmental governance, ways the state can effectively address telecoupled environmental issues both within and beyond national borders are addressed, drawing on the example of soy trade between Brazil and Germany. This builds on recent contributions to the literature on governance of interregional ecological challenges to elaborate potential policy and governance options, ranging from classical bilateral, multilateral, and international agreements, to information-based, economic, and hybrid governance modes. While telecoupled environmental problems create governance challenges related to scale, knowledge gaps, coordination, and state capacity, the state has an important role to play. To explore this further, interdisciplinary inquiry is required that includes but moves beyond the state.